Preparation method and application of brominated flame retardant masterbatch

By dissolving high melting point DBDPE into low melting point OBDPE, adding active ultra-fine ferrous carbonate, and combining ball milling and high-speed stirring technology, the brominated flame retardant is evenly dispersed in the resin and solves the problem of HBr gas and poor dispersion. problem, improving the heat resistance temperature and mechanical properties.

CN117986633BActive Publication Date: 2025-01-21EAST CHINA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410149198.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-02
Publication Date
2025-01-21
Estimated Expiration
2044-02-02

AI Technical Summary

Technical Problem

The existing bromine flame retardant produces harmful gas HBr under high combustion temperature conditions, and has large particle size and poor dispersion, resulting in high usage, high cost and reduced mechanical properties.

Method used

By dissolving high melting point decabromodiphenyl ethane (DBDPE) into low melting point octabromodiphenyl ethane (OBDPE) and adding active ultrafine ferrous carbonate to form a molecular level/nanoscale mixture, Combining technologies such as ball milling and high-speed stirring, the flame retardant can be evenly dispersed in the resin.

Benefits of technology

The hazards of HBr gas are eliminated, the amount of flame retardant is reduced, the heat-resistant temperature of the resin is increased, the production cost is reduced, and the flame retardant performance and mechanical properties are significantly improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a bromine flame retardant masterbatch, belonging to the technical field of thermoplastic resin flame retardant, adding OBDPE and DBDPE into a reactor, forming a DBDPE-OBDPE solution DOS, adding active ultrafine ferrous carbonate, stirring and mixing evenly, breaking into primary powder after cooling, and putting into a full-scale planetary ball mill with a synergistic flame retardant and an acid absorber for ball milling, the mixed flame retardant after ball milling is mixed with a compatibilizer, a lubricant, and a dried resin, added to the hopper of a screw extruder, extruded, granulated, and a bromine flame retardant masterbatch is obtained, and then mixed with a resin, glass fiber is added, extruded by a screw extruder, and a strip is obtained, achieving high flame retardant performance and mechanical properties. The flame retardant masterbatch prepared by the present invention realizes molecular level / nanoscale dispersion between the resin, eliminates the pollution of HBr gas to the environment, reduces the amount of flame retardant, improves the heat-resistant temperature of the resin, enhances the mechanical properties of the material, and reduces production costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermoplastic resin flame retardancy, and in particular to a preparation method of a bromine flame retardant masterbatch and application thereof. Background Art

[0002] Thermoplastic resins are widely used in the automotive industry, aerospace, infrastructure and optoelectronics industries. Glass fiber reinforced resins have the advantages of light weight, corrosion resistance and significantly improved mechanical properties. At present, glass fiber reinforced thermoplastic composites have higher requirements for flame retardancy in practical applications. Flame retardants that can be used for glass fiber reinforced thermoplastic resins include metal hydroxide flame retardants, nitrogen (N) flame retardants, phosphorus (P) flame retardants, PN flame retardants (also known as intumescent flame retardants) and bromine flame retardants. Among them, bromine flame retardants have good stability, small addition amount, good compatibility with resin materials, and little effect on the mechanical properties of resins. However, HBr gas will be generated under high temperature conditions of combustion, and decabromodiphenyl ether flame retardants also generate harmful substances such as polybrominated dibenzofuran (PBDF) / polybrominated dibenzo dioxins (PBDD) during the flame retardant process, so they are restricted by RoHS (Restriction of Hazardous Substances).

[0003] However, a large number of studies have shown that decabromodiphenyl ethane (DBDPE) does not contain ether bonds, does not generate PBDF / PBDD, and has flame retardant properties similar to decabromodiphenyl ether, making DBDPE a broad-spectrum additive flame retardant, usually used in synergy with antimony trioxide (AO). However, DBDPE has a high melting point (357 °C), does not melt during screw extrusion, and has a large original particle size (2 μm -50 μm), which makes the flame retardant DBDPE poorly dispersible in the resin melt, large addition amounts, high raw material costs, and reduced mechanical properties of the composite material. Octabromodiphenyl ethane (OBDPE) has a similar molecular structure to DBDPE and has similar flame retardant properties to DBDPE, but because there are 2 fewer Br atoms in each molecule, its flame retardant properties are about 25% lower than DBDPE.

[0004] How to give full play to the advantages of DBDPE, reduce the particle size of DBDPE, enhance the dispersion performance of DBDPE in resin, and eliminate the harm of HBr gas at the same time has become an urgent problem to be solved. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method and application of a bromine flame retardant masterbatch, so as to solve the comprehensive problems of high dosage, poor dispersibility and generation of HBr gas of bromine flame retardant. The method dissolves a high melting point flame retardant DBDPE in a low melting point OBDPE, uses active ultrafine ferrous carbonate to prevent solidification phase separation, and realizes molecular level / nanoscale dispersion with resin, thereby eliminating the pollution of HBr gas to the environment, reducing the dosage of flame retardant, improving the heat resistance temperature of resin and reducing production cost.

[0006] To achieve the above object, the present invention provides a method for preparing a brominated flame retardant masterbatch, which specifically comprises the following steps:

[0007] S1, put octabromodiphenyl ether OBDPE and decabromodiphenyl ethane DBDPE powder into a reactor, heat up until OBDPE melts, OBDPE liquid dissolves DBDPE to form DBDPE-OBDPE solution DOS, add active ultrafine ferrous carbonate powder to DOS under strong stirring, stir and mix evenly to form a dispersion slurry, discharge the slurry while hot, cool to obtain a solid mixture of DBDPE, active ultrafine ferrous carbonate powder and OBDPE that is uniformly dispersed at the molecular level / nanoscale, and crush it into primary powder;

[0008] S2, putting the primary powder of the mixture obtained in step S1, the synergistic flame retardant and the acid absorbent into an omnidirectional planetary ball mill according to a certain proportion, and milling them to obtain a mixed flame retardant;

[0009] S3, placing the mixed flame retardant obtained in step S2, the compatibilizer, the lubricant, and the dry resin in a high-speed mixer and mixing them evenly;

[0010] S4, adding the mixture obtained in step S3 into the hopper of a screw extruder, extruding, and granulating to obtain a brominated flame retardant masterbatch.

[0011] Preferably, in step S1, the mass ratio of DBDPE to OBDPE is 1:1 - 5:1, and the temperature of melting OBDPE and dissolving DBDPE in the reactor to form liquid DOS is 170 - 200 °C.

[0012] Preferably, the active ultrafine ferrous carbonate in step S1 is an ultrafine powder surface-modified with hexadecyltrimethylammonium bromide, sodium dodecylsulfonate, a silane coupling agent, and a titanate coupling agent, the particle size of the ultrafine ferrous carbonate is in the range of 100 nm to 900 nm, and the amount of ferrous carbonate added is 0.25 wt% to 5.5 wt% of the total mass of OBDPE and DBDPE.

[0013] Preferably, the synergistic flame retardant in step S2 is AO, the acid absorber is HT or talcum powder, and the contents of the primary powder of the mixture, the synergistic flame retardant and the acid absorber in the mixed flame retardant account for 20%-50%, 10%-15% and 0%-20% of the flame retardant masterbatch content, respectively.

[0014] Preferably, the compatibilizer in step S3 is a chemically modified polymer containing carboxyl, anhydride, hydroxyl and ketone groups, accounting for 2% of the flame retardant masterbatch content, and the lubricant is stearic acid and silicone masterbatch, and stearic acid and silicone masterbatch account for 1.1% and 0.9% of the flame retardant masterbatch content, respectively.

[0015] Preferably, the resin in step S3 is one of polyethylene, polypropylene, polystyrene, polyamide, polycarbonate, polyethylene terephthalate and polymethyl methacrylate.

[0016] Preferably, the maximum extrusion temperature of the screw extruder in step S4 is 10-20° C. higher than the melting point of the resin.

[0017] The invention provides an application of a bromine-based flame retardant masterbatch, and the prepared bromine-based flame retardant masterbatch is used to flame retard a thermoplastic resin.

[0018] The present invention also provides an application of a brominated flame retardant masterbatch, wherein the flame retardant masterbatch is mixed with a resin, and glass fiber is added, wherein the flame retardant masterbatch accounts for 10%-30% of the total addition amount, and the glass fiber accounts for 10%-50% of the total addition amount, and the mixture is extruded through a screw extruder to obtain a brominated flame retardant strip.

[0019] Therefore, the present invention adopts the above-mentioned method for preparing a brominated flame retardant masterbatch and its application, which has the following beneficial effects:

[0020] (1) Taking advantage of the fact that the melting point of OBDPE is lower than the melting temperature of the resin, the molten liquid OBDPE is used to dissolve DBDPE to achieve molecular level / nanoscale mixing. Similarly, taking advantage of the fact that the melting point of OBDPE is lower than the melting temperature of the resin, DBDPE with a melting point higher than the melting point of the resin can be dispersed and mixed in the resin at a near molecular level / nanoscale.

[0021] (2) After surface modification, active ultrafine ferrous carbonate has good affinity with OBDPE and DBDPE. When active ultrafine ferrous carbonate is added to the OBDPE and DBDPE system, the solidification phase separation of OBDPE and DBDPE can be prevented after cooling and solidification.

[0022] (3) Ferrous carbonate generates CO2 under high temperature conditions during combustion, which has a flame retardant effect. The generated Fe2O3 undergoes redox reaction with HBr generated under high temperature conditions to generate Fe. Fe catalyzes the resin to generate crystalline carbon with a graphene structure. The crystalline carbon has a higher oxygen resistance and plays a flame retardant role. At the same time, Br reacts with the synergistic flame retardant Sb2O3, hydrotalcite or talc to generate metal bromide, eliminating the release of HBr gas.

[0023] (4) Hydrotalcite or talcum powder reacts with HBr to generate AlBr3 and MgBr2, eliminating the harm of HBr gas. At the same time, AlBr3 also has good flame retardant properties.

[0024] (5) Brominated flame retardants generally require the addition of antimony trioxide synergistic flame retardant. In order to make the flame retardants mix more evenly and disperse better in the resin, the flame retardants are mixed by ball milling. This not only greatly reduces the particle size, but also forms a supramolecular structure between the flame retardants. It not only improves the dispersion of the flame retardant in the resin, reduces the amount of flame retardant used, and increases the heat resistance of the resin, but also makes the flame retardant exhibit a thermal decomposition temperature that is completely different from that of a single flame retardant, thereby improving the flame retardant performance.

[0025] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further illustrated by the following examples.

[0027] In order to explain the present invention more clearly, the technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, which are only used as an explanation of the present invention and do not limit the scope of the present invention.

[0028] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0029] Example 1

[0030] A preparation and application of a brominated flame retardant masterbatch, specifically comprising the following steps:

[0031] S1. Put DBDPE and OBDPE powders with a mass ratio of 5:1 into a reactor, heat it to 180 °C, melt OBDPE, and dissolve DBDPE in the molten OBDPE liquid to form liquid DOS. Under strong stirring, add 0.25 wt% of the total mass of OBDPE and DBDPE to DOS, stir and mix evenly to form a stable dispersion slurry, discharge the slurry while hot, cool it to obtain a molecular level / nanoscale mixed, uniformly dispersed DBDPE, active ultrafine ferrous carbonate and OBDPE solid mixture, and crush it into primary powder;

[0032] S2, weighing the mixture obtained in step S1 with a flame retardant masterbatch content of 50%, the synergistic flame retardant AO with a flame retardant masterbatch content of 10%, and the acid absorbent HT with a flame retardant masterbatch content of 5%, and putting them into an omnidirectional planetary ball mill for ball milling for 4 hours;

[0033] S3, placing the flame retardant obtained in step S2, 2% of a compatibilizer, 1.1% of stearic acid, 0.9% of a silicone masterbatch and 30% of dry polypropylene in a high-speed mixer and mixing them evenly;

[0034] S4, adding the mixture obtained in step S3 into the hopper of a screw extruder, extruding, and granulating to obtain a brominated flame retardant masterbatch, which is used as a flame retardant for polypropylene resin;

[0035] S5. Mix 30% of the flame retardant masterbatch obtained in step S4, 20% of the glass fiber and 50% of the dry polypropylene, and form a specimen through a screw extruder to test the flame retardant property and mechanical property.

[0036] The vertical combustion level of the sample obtained at this time is UL-94 V-0 level, and the mechanical properties are improved by 34%.

[0037] Example 2

[0038] A preparation and application of a brominated flame retardant masterbatch, specifically comprising the following steps:

[0039] S1. Put DBDPE and OBDPE powders with a mass ratio of 1:1 into a reactor, heat it to 170 °C, melt OBDPE, and dissolve DBDPE in the molten OBDPE liquid to form liquid DOS. Under strong stirring, add 2 wt% of the total mass of OBDPE and DBDPE active ultrafine ferrous carbonate powder to DOS, stir and mix evenly to form a stable dispersion slurry, discharge the slurry while hot, cool it to obtain a molecular level / nanoscale mixed, uniformly dispersed solid mixture of DBDPE, active ultrafine ferrous carbonate and OBDPE, and crush it into primary powder;

[0040] S2, weighing the mixture obtained in step S1 with a flame retardant masterbatch content of 35%, the synergistic flame retardant AO with a flame retardant masterbatch content of 15%, and the acid absorbent talc with a flame retardant masterbatch content of 10%, and putting them into an omnidirectional planetary ball mill for 4 hours;

[0041] S3, placing the flame retardant obtained in step S2, 2% of a compatibilizer, 1.1% of stearic acid, 0.9% of a silicone masterbatch and 35% of dry polyethylene in a high-speed mixer and mixing them evenly;

[0042] S4, adding the mixture obtained in step S3 into the hopper of a screw extruder, extruding, and granulating to obtain a brominated flame retardant masterbatch for use as a flame retardant for polyethylene resin;

[0043] S5. Mix 30% of the flame retardant masterbatch obtained in step S4, 10% of the glass fiber and 60% of the dried polyethylene, and form a specimen through a screw extruder to test the flame retardant properties and mechanical properties.

[0044] The vertical combustion level of the sample obtained at this time is UL-94 V-0 level, and the mechanical properties are improved by 21%.

[0045] Example 3

[0046] A preparation and application of a brominated flame retardant masterbatch, specifically comprising the following steps:

[0047] S1. Put DBDPE and OBDPE powders with a mass ratio of 2:1 into a reactor, heat it to 180 °C, melt OBDPE, and dissolve DBDPE in the molten OBDPE liquid to form liquid DOS. Under strong stirring, add 4 wt% of the total mass of OBDPE and DBDPE to DOS, stir and mix evenly to form a stable dispersion slurry, discharge the slurry while hot, cool it to obtain a molecular level / nanoscale mixed, uniformly dispersed DBDPE, active ultrafine ferrous carbonate and OBDPE solid mixture, and crush it into primary powder;

[0048] S2, weighing the mixture obtained in step S1 with a flame retardant masterbatch content of 25%, the synergistic flame retardant AO with a flame retardant masterbatch content of 12%, and the acid absorbent HT with a flame retardant masterbatch content of 15%, and putting them into an omnidirectional planetary ball mill for ball milling for 4 hours;

[0049] S3, placing the flame retardant obtained in step S2, 2% of a compatibilizer, 1.1% of stearic acid, 0.9% of a silicone masterbatch and 43% of dry polypropylene in a high-speed mixer and mixing them evenly;

[0050] S4, adding the mixture obtained in step S3 into the hopper of a screw extruder, extruding, and granulating to obtain a brominated flame retardant masterbatch, which is used as a flame retardant for polypropylene resin;

[0051] S5, mixing 25% of the flame retardant masterbatch obtained in step S4, 50% of the glass fiber and 30% of the dried polypropylene, forming a specimen through a screw extruder, and testing the flame retardant property and mechanical property.

[0052] The vertical combustion level of the sample obtained at this time is UL-94 V-0 level, and the mechanical properties are improved by 78%.

[0053] Example 4

[0054] A preparation and application of a brominated flame retardant masterbatch, specifically comprising the following steps:

[0055] S1. Put DBDPE and OBDPE powders with a mass ratio of 5:1 into a reactor, heat it to 170 °C, melt OBDPE, and dissolve DBDPE in the molten OBDPE liquid to form liquid DOS. Add 5 wt% of the total mass of OBDPE and DBDPE to DOS under strong stirring, stir and mix evenly to form a stable dispersion slurry, discharge the slurry while hot, cool it to obtain a molecular level / nanoscale mixed, uniformly dispersed DBDPE, active ultrafine ferrous carbonate and OBDPE solid mixture, and crush it into primary powder;

[0056] S2, weighing the mixture obtained in step S1 with a flame retardant masterbatch content of 40%, the synergistic flame retardant AO with a flame retardant masterbatch content of 10%, and the acid absorbent HT with a flame retardant masterbatch content of 15%, and putting them into an omnidirectional planetary ball mill for 4 hours;

[0057] S3, placing the flame retardant obtained in step S2, 2% of a compatibilizer, 1.1% of stearic acid, 0.9% of a silicone masterbatch and 30% of dried polycarbonate in a high-speed mixer and mixing them evenly;

[0058] S4, adding the mixture obtained in step S3 into the hopper of a screw extruder, extruding, and granulating to obtain a brominated flame retardant masterbatch for use as a flame retardant for polycarbonate resin;

[0059] S5, mixing 25% of the flame retardant masterbatch obtained in step S4, 10% of the glass fiber and 65% of the dried polycarbonate, forming a specimen through a screw extruder, and testing the flame retardant property and mechanical property.

[0060] The vertical combustion level of the sample obtained at this time is UL-94 V-0 level, and the mechanical properties are improved by 18%.

[0061] Example 5

[0062] A preparation and application of a brominated flame retardant masterbatch, specifically comprising the following steps:

[0063] S1. Put DBDPE and OBDPE powders with a mass ratio of 3:1 into a reactor, heat it to 200 °C, melt OBDPE, and dissolve DBDPE in the molten OBDPE liquid to form liquid DOS. Under strong stirring, add 5.5 wt% of the total mass of OBDPE and DBDPE to DOS, stir and mix evenly to form a stable dispersion slurry, discharge the slurry while hot, cool it to obtain a molecular level / nanoscale mixed, uniformly dispersed solid mixture of DBDPE, active ultrafine ferrous carbonate and OBDPE, and crush it into primary powder;

[0064] S2, weighing the mixture obtained in step S1 with a flame retardant masterbatch content of 50%, the synergistic flame retardant AO with a flame retardant masterbatch content of 10%, and the acid absorbent talc with a flame retardant masterbatch content of 5%, and putting them into an omnidirectional planetary ball mill for 4 hours;

[0065] S3, placing the flame retardant obtained in step S2, 2% of a compatibilizer, 1.1% of stearic acid, 0.9% of a silicone masterbatch and 30% of dry polypropylene in a high-speed mixer and mixing them evenly;

[0066] S4, adding the mixture obtained in step S3 into the hopper of a screw extruder, extruding, and granulating to obtain a brominated flame retardant masterbatch, which is used as a flame retardant for polypropylene resin;

[0067] S5, mixing 15% of the flame retardant masterbatch obtained in step S4, 30% of the glass fiber and 55% of the dry polypropylene, forming a specimen through a screw extruder, and testing the flame retardant property and mechanical property.

[0068] The vertical combustion level of the sample obtained at this time is UL-94 V-0 level, and the mechanical properties are improved by 35%.

[0069] Example 6

[0070] A preparation and application of a brominated flame retardant masterbatch, specifically comprising the following steps:

[0071] S1. Put DBDPE and OBDPE powders with a mass ratio of 4:1 into a reactor, heat it to 200 °C, melt OBDPE, and dissolve DBDPE in the molten OBDPE liquid to form liquid DOS. Under strong stirring, add 3.5 wt% of the total mass of OBDPE and DBDPE to DOS, stir and mix evenly to form a stable dispersion slurry, discharge the slurry while hot, cool it to obtain a molecular level / nanoscale mixed, uniformly dispersed solid mixture of DBDPE, active ultrafine ferrous carbonate and OBDPE, and crush it into primary powder;

[0072] S2, weighing the mixture obtained in step S1 with a flame retardant masterbatch content of 45% and the synergistic flame retardant AO with a flame retardant masterbatch content of 15%, and putting them into an omnidirectional planetary ball mill for ball milling for 4 hours;

[0073] S3, placing the flame retardant obtained in step S2, 2% of a compatibilizer, 1.1% of stearic acid, 0.9% of a silicone masterbatch and 35% of dried polyamide in a high-speed mixer and mixing them evenly;

[0074] S4, adding the mixture obtained in step S3 into the hopper of a screw extruder, extruding, and granulating to obtain a brominated flame retardant masterbatch for use as a flame retardant for polyamide resin;

[0075] S5. Mix 30% of the flame retardant masterbatch obtained in step S4, 20% of the glass fiber and 50% of the dried polyamide, and form a specimen through a screw extruder to test the flame retardant property and mechanical property.

[0076] The vertical combustion level of the sample obtained at this time is UL-94 V-0 level, and the mechanical properties are improved by 32%.

[0077] Example 7

[0078] A preparation and application of a brominated flame retardant masterbatch, specifically comprising the following steps:

[0079] S1. Put DBDPE and OBDPE powders with a mass ratio of 2:1 into a reactor, heat it to 190 °C, melt OBDPE, and dissolve DBDPE in the molten OBDPE liquid to form liquid DOS. Under strong stirring, add 1 wt% of the total mass of OBDPE and DBDPE active ultrafine ferrous carbonate powder to DOS, stir and mix evenly to form a stable dispersion slurry, discharge the slurry while hot, cool it to obtain a molecular level / nanoscale mixed, uniformly dispersed DBDPE, active ultrafine ferrous carbonate and OBDPE solid mixture, and crush it into primary powder;

[0080] S2, weighing the mixture obtained in step S1 with a flame retardant masterbatch content of 35%, the synergistic flame retardant AO with a flame retardant masterbatch content of 12%, and the acid absorbent HT with a flame retardant masterbatch content of 15%, and putting them into an omnidirectional planetary ball mill for 4 hours;

[0081] S3, placing the flame retardant obtained in step S2, 2% of a compatibilizer, 1.1% of stearic acid, 0.9% of a silicone masterbatch and 33% of dry polypropylene in a high-speed mixer and mixing them evenly;

[0082] S4, adding the mixture obtained in step S3 into the hopper of a screw extruder, extruding, and granulating to obtain a brominated flame retardant masterbatch, which is used as a flame retardant for polypropylene resin;

[0083] S5. Mix 20% of the flame retardant masterbatch obtained in step S4, 10% of the glass fiber and 70% of the dry polypropylene, and form a specimen through a screw extruder to test the flame retardant property and mechanical property.

[0084] The vertical combustion level of the sample obtained at this time is UL-94 V-0 level, and the mechanical properties are improved by 22%.

[0085] Example 8

[0086] A preparation and application of a brominated flame retardant masterbatch, specifically comprising the following steps:

[0087] S1. Put DBDPE and OBDPE powders with a mass ratio of 1:1 into a reactor, heat it to 180 °C, melt OBDPE, and dissolve DBDPE in the molten OBDPE liquid to form liquid DOS. Under strong stirring, add 1.5 wt% of the total mass of OBDPE and DBDPE active ultrafine ferrous carbonate powder to DOS, stir and mix evenly to form a stable dispersion slurry, discharge the slurry while hot, cool it to obtain a molecular level / nanoscale mixed, uniformly dispersed DBDPE, active ultrafine ferrous carbonate and OBDPE solid mixture, and crush it into primary powder;

[0088] S2, weighing the mixture obtained in step S1 with a flame retardant masterbatch content of 40%, the synergistic flame retardant AO with a flame retardant masterbatch content of 15%, and the acid absorbent HT with a flame retardant masterbatch content of 10%, and putting them into an omnidirectional planetary ball mill for 4 hours;

[0089] S3, placing the flame retardant obtained in step S2, 2% of a compatibilizer, 1.1% of stearic acid, 0.9% of a silicone masterbatch and 30% of dried polyethylene terephthalate in a high-speed mixer and mixing them evenly;

[0090] S4, adding the mixture obtained in step S3 into the hopper of a screw extruder, extruding, and granulating to obtain a brominated flame retardant masterbatch, which is used as a flame retardant for polyethylene terephthalate resin;

[0091] S5. Mix 15% of the flame retardant masterbatch obtained in step S4, 20% of the glass fiber and 65% of the dried polyethylene terephthalate, and form a strip through a screw extruder to test the flame retardant property and mechanical property.

[0092] The vertical combustion level of the sample obtained at this time is UL-94 V-0 level, and the mechanical properties are improved by 37%.

[0093] Example 9

[0094] A preparation and application of a brominated flame retardant masterbatch, specifically comprising the following steps:

[0095] S1. Put DBDPE and OBDPE powders with a mass ratio of 4:1 into a reactor, heat it to 170 °C, melt OBDPE, and dissolve DBDPE in the molten OBDPE liquid to form liquid DOS. Under strong stirring, add 0.25 wt% of the total mass of OBDPE and DBDPE to DOS, stir and mix evenly to form a stable dispersion slurry, discharge the slurry while hot, cool it to obtain a molecular level / nanoscale mixed, uniformly dispersed solid mixture of DBDPE, active ultrafine ferrous carbonate and OBDPE, and crush it into primary powder;

[0096] S2, weighing the mixture obtained in step S1 with a flame retardant masterbatch content of 40%, the synergistic flame retardant AO with a flame retardant masterbatch content of 10%, and the acid absorbent HT with a flame retardant masterbatch content of 5%, and putting them into an omnidirectional planetary ball mill for 4 hours;

[0097] S3, placing the flame retardant obtained in step S2, 2% of a compatibilizer, 1.1% of stearic acid, 0.9% of a silicone masterbatch and 40% of dry polypropylene in a high-speed mixer and mixing them evenly;

[0098] S4, adding the mixture obtained in step S3 into the hopper of a screw extruder, extruding, and granulating to obtain a brominated flame retardant masterbatch, which is used as a flame retardant for polypropylene resin;

[0099] S5. 10% of the flame retardant masterbatch obtained in step S4, 50% of the glass fiber and 40% of the dried polypropylene are mixed, and the mixture is formed into strips by a screw extruder, and the flame retardant properties and mechanical properties are tested.

[0100] The vertical combustion level of the sample obtained at this time is UL-94 V-0 level, and the mechanical properties are improved by 82%.

[0101] Example 10

[0102] A preparation and application of a brominated flame retardant masterbatch, specifically comprising the following steps:

[0103] S1. Put DBDPE and OBDPE powders with a mass ratio of 3:1 into a reactor, heat it to 190 °C, melt OBDPE, and dissolve DBDPE in the molten OBDPE liquid to form liquid DOS. Under strong stirring, add 5.5 wt% of the total mass of OBDPE and DBDPE to DOS, stir and mix evenly to form a stable dispersion slurry, discharge the slurry while hot, cool it to obtain a molecular level / nanoscale mixed, uniformly dispersed DBDPE, active ultrafine ferrous carbonate and OBDPE solid mixture, and crush it into primary powder;

[0104] S2, weighing the mixture obtained in step S1 with a flame retardant masterbatch content of 35%, the synergistic flame retardant AO with a flame retardant masterbatch content of 12%, and the acid absorbent HT with a flame retardant masterbatch content of 20%, and putting them into an omnidirectional planetary ball mill for ball milling for 4 hours;

[0105] S3, placing the flame retardant obtained in step S2, 2% of a compatibilizer, 1.1% of stearic acid, 0.9% of a silicone masterbatch and 28% of dry polystyrene in a high-speed mixer and mixing them evenly;

[0106] S4, adding the mixture obtained in step S3 into the hopper of a screw extruder, extruding, and granulating to obtain a brominated flame retardant masterbatch for use as a flame retardant for polystyrene resin;

[0107] S5. Mix 30% of the flame retardant masterbatch obtained in step S4, 40% of the glass fiber and 30% of the dried polystyrene, and form a specimen through a screw extruder to test the flame retardant properties and mechanical properties.

[0108] The vertical combustion level of the sample obtained at this time is UL-94 V-0 level, and the mechanical properties are improved by 63%.

[0109] Embodiment 11

[0110] A preparation and application of a brominated flame retardant masterbatch, specifically comprising the following steps:

[0111] S1. Put DBDPE and OBDPE powders with a mass ratio of 2:1 into a reactor, heat it to 190 °C, melt OBDPE, and dissolve DBDPE in the molten OBDPE liquid to form liquid DOS. Under strong stirring, add 2.25 wt% of the total mass of OBDPE and DBDPE to DOS, stir and mix evenly to form a stable dispersion slurry, discharge the slurry while hot, cool it to obtain a molecular level / nanoscale mixed, uniformly dispersed DBDPE, active ultrafine ferrous carbonate and OBDPE solid mixture, and crush it into primary powder;

[0112] S2, weighing the mixture obtained in step S1 with a flame retardant masterbatch content of 45%, the synergistic flame retardant AO with a flame retardant masterbatch content of 15%, and the acid absorbent talc with a flame retardant masterbatch content of 5%, and putting them into an omnidirectional planetary ball mill for 4 hours;

[0113] S3, placing the flame retardant obtained in step S2, 2% of a compatibilizer, 1.1% of stearic acid, 0.9% of a silicone masterbatch and 30% of dry polymethyl methacrylate in a high-speed mixer and mixing them evenly;

[0114] S4, adding the mixture obtained in step S3 into the hopper of a screw extruder, extruding, and granulating to obtain a brominated flame retardant masterbatch for use as a flame retardant for polymethyl methacrylate resin;

[0115] S5. Mix 30% of the flame retardant masterbatch obtained in step S4, 10% of the glass fiber and 60% of the dried polymethyl methacrylate, and form a specimen through a screw extruder to test the flame retardant properties and mechanical properties.

[0116] The vertical combustion level of the specimens obtained at this time is UL-94 V-0 level, and the mechanical properties are improved by 18%.

[0117] Example 12

[0118] A preparation and application of a brominated flame retardant masterbatch, specifically comprising the following steps:

[0119] S1. Put DBDPE and OBDPE powders with a mass ratio of 3:1 into a reactor, heat it to 200 °C, melt OBDPE, and dissolve DBDPE in the molten OBDPE liquid to form liquid DOS. Under strong stirring, add 4.5 wt% of the total mass of OBDPE and DBDPE to DOS, stir and mix evenly to form a stable dispersion slurry, discharge the slurry while hot, cool it to obtain a molecular level / nanoscale mixed, uniformly dispersed solid mixture of DBDPE, active ultrafine ferrous carbonate and OBDPE, and crush it into primary powder;

[0120] S2, weighing the mixture obtained in step S1 with a flame retardant masterbatch content of 40%, the synergistic flame retardant AO with a flame retardant masterbatch content of 12%, and the acid absorbent HT with a flame retardant masterbatch content of 15%, and putting them into an omnidirectional planetary ball mill for 4 hours;

[0121] S3, placing the flame retardant obtained in step S2, 2% of a compatibilizer, 1.1% of stearic acid, 0.9% of a silicone masterbatch and 28% of dry polystyrene in a high-speed mixer and mixing them evenly;

[0122] S4, adding the mixture obtained in step S3 into the hopper of a screw extruder, extruding, and granulating to obtain a brominated flame retardant masterbatch for use as a flame retardant for polystyrene resin;

[0123] S5, mixing 25% of the flame retardant masterbatch obtained in step S4, 20% of the glass fiber and 55% of the dried polystyrene, forming a specimen through a screw extruder, and testing the flame retardant property and mechanical property.

[0124] The vertical combustion level of the sample obtained at this time is UL-94 V-0 level, and the mechanical properties are improved by 42%.

[0125] Comparative Example 1

[0126] S1. Weigh the flame retardants DBDPE and OBDPE, active ultrafine ferrous carbonate, synergistic flame retardant AO, and acid absorbent HT and put them into a full-range planetary ball mill for 4 hours. Among them, the mass ratio of DBDPE and OBDPE is 5:1, accounting for 50wt% of the mass of the flame retardant masterbatch; the active ultrafine ferrous carbonate accounts for 0.25 wt% of the total mass of OBDPE and DBDPE, and AO and HT account for 10% and 5% of the mass of the flame retardant masterbatch, respectively.

[0127] S2, the flame retardant obtained in step S1 is placed in a high-speed mixer and mixed evenly with a compatibilizer, stearic acid, silicone masterbatch and dried polypropylene, wherein the compatibilizer, stearic acid, silicone masterbatch and polypropylene account for 2%, 1.1%, 0.9% and 30% of the mass of the flame retardant masterbatch, respectively.

[0128] S3, adding the mixture obtained in step S2 into the hopper of a screw extruder, extruding and granulating to obtain a flame retardant masterbatch for use as a flame retardant for polypropylene resin;

[0129] S4, mixing glass fiber, dried polypropylene and the flame retardant masterbatch obtained in step S3, forming a sample bar through a screw extruder, and testing the flame retardant property and mechanical property. Among them, the glass fiber, polypropylene and flame retardant masterbatch account for 20%, 50% and 30% of the sample bar mass respectively.

[0130] The vertical combustion level of the obtained sample strip is UL-94 V-1 level, and the mechanical properties are improved by 27%. Compared with Example 1, it can be seen that when the flame retardants OBDPE and DBDPE are directly mixed with other substances and added to the matrix, the flame retardants are unevenly dispersed and have large particle sizes during the extrusion process, and the mechanical properties are reduced by 7% compared with Example 1, and the flame retardant properties of the sample strip are reduced to UL-94 V-1 level.

[0131] Comparative Example 2

[0132] S1. Weigh DBDPE and OBDPE powders in a mass ratio of 5:1, add them into a reactor, heat to 180 °C to melt OBDPE, and at the same time, the molten OBDPE liquid dissolves DBDPE to form liquid DOS. Add 0.25% active ultrafine ferrous carbonate under stirring to form a stable dispersion, discharge the reactor while hot, cool to obtain a solid mixture, and crush it into powder.

[0133] S2, weigh the synergistic flame retardant AO, the acid absorber HT, the compatibilizer, stearic acid, the silicone masterbatch, the polypropylene and the powder obtained in step S1 and put them into a high-speed mixer and mix them evenly. Among them, AO, HT, the compatibilizer, stearic acid, the silicone masterbatch, the polypropylene and the powder obtained in S1 account for 10%, 5%, 2%, 1.1%, 0.9%, 30% and 50% of the mass of the flame retardant masterbatch, respectively.

[0134] S3, adding the mixture obtained in step S2 into the hopper of a screw extruder, extruding and granulating to obtain a flame retardant masterbatch for use as a flame retardant for polypropylene resin;

[0135] S4, mixing glass fiber, dried polypropylene and the flame retardant masterbatch obtained in step S3, forming a sample bar through a screw extruder, and testing the flame retardant property and mechanical property. Among them, the glass fiber, polypropylene and flame retardant masterbatch account for 20%, 50% and 30% of the sample bar mass respectively.

[0136] The vertical combustion level of the obtained sample bar is UL-94 V-1 level, and the mechanical properties are improved by 21%. Compared with Example 1, it can be seen that when the flame retardant and other powders are not ball-milled, the flame retardant has a large particle size and poor dispersion in the sample bar. Although ultrafine activated ferrous carbonate is added, the flame retardancy still does not reach V-0 level, and the mechanical properties are reduced by 13% compared with Example 1.

[0137] Comparative Example 3

[0138] S1. Weigh flame retardants DBDPE and OBDPE and add them into a reactor. Heat to 180°C under stirring to melt OBDPE and dissolve DBDPE to obtain a solution of the two. Discharge the solution from the reactor while hot and cool to obtain a solid mixture, which is crushed into powder.

[0139] S2, weigh the synergistic flame retardant AO, the acid absorber HT and the powder obtained from S1, put them into a full-range planetary ball mill and mill them for 4 hours. Among them, the mass ratio of DBDPE and OBDPE is 5:1, accounting for 50 wt% of the mass of the flame retardant masterbatch; AO and HT account for 10% and 5% of the mass of the flame retardant masterbatch respectively.

[0140] S3, the flame retardant obtained in step S1 is placed in a high-speed mixer and mixed evenly with a compatibilizer, stearic acid, silicone masterbatch and dried polypropylene, wherein the compatibilizer, stearic acid, silicone masterbatch and polypropylene account for 2%, 1.1%, 0.9% and 30% of the mass of the flame retardant masterbatch, respectively.

[0141] S4, adding the mixture obtained in step S3 into the hopper of a screw extruder, extruding, and granulating to obtain a flame retardant masterbatch for use as a flame retardant for polypropylene resin;

[0142] S5, mixing glass fiber, dried polypropylene and the flame retardant masterbatch obtained in step S3, forming a sample bar through a screw extruder, and testing the flame retardant property and mechanical property. Among them, the glass fiber, polypropylene and flame retardant masterbatch account for 20%, 50% and 30% of the sample bar mass respectively.

[0143] The vertical combustion level of the obtained sample is UL-94 V-1 level, and the mechanical properties are improved by 30%. Compared with Example 1, it can be seen that without adding ultrafine active iron carbonate to the flame retardant, the mechanical properties are reduced by 4%, but the flame retardant properties of the sample are reduced to UL-94 V-1 level.

[0144] Comparative Example 4

[0145] S1. Weigh the flame retardant DBDPE, synergistic flame retardant AO, and acid absorbent HT and put them into a full-range planetary ball mill for 4 hours. DBDPE, AO, and HT account for 50%, 10%, and 5% of the mass of the flame retardant masterbatch, respectively.

[0146] S2, the flame retardant obtained in step S1 is placed in a high-speed mixer and mixed evenly with a compatibilizer, stearic acid, silicone masterbatch and dried polypropylene, wherein the compatibilizer, stearic acid, silicone masterbatch and polypropylene account for 2%, 1.1%, 0.9% and 30% of the mass of the flame retardant masterbatch, respectively.

[0147] S3, adding the mixture obtained in step S2 into the hopper of a screw extruder, extruding and granulating to obtain a flame retardant masterbatch for use as a flame retardant for polypropylene resin;

[0148] S4, mixing glass fiber, dried polypropylene and the flame retardant masterbatch obtained in step S3, forming a sample bar through a screw extruder, and testing the flame retardant property and mechanical property. Among them, the glass fiber, polypropylene and flame retardant masterbatch account for 20%, 50% and 30% of the sample bar mass respectively.

[0149] The vertical combustion level of the obtained sample strip is UL-94 V-1 level, and the mechanical properties are improved by 25%. Compared with Example 1, it can be seen that the flame retardant does not add ultrafine active iron carbonate, and does not add OBDPE melt dissolution DBDPE, the flame retardant is unevenly dispersed and has a large particle size during the extrusion process, and the mechanical properties are reduced by 9% compared with Example 1, and the flame retardant performance of the sample strip is reduced to UL-94 V-1 level.

[0150] Comparative Example 5

[0151] S1. Mix the flame retardant DBDPE, compatibilizer, stearic acid, silicone masterbatch and dried polypropylene in a high-speed mixer. Among them, DBDPE, compatibilizer, stearic acid, silicone masterbatch and polypropylene account for 50%, 2%, 1.1%, 0.9% and 30% of the mass of the flame retardant masterbatch respectively.

[0152] S2, adding the mixture obtained in step S1 into the hopper of a screw extruder, extruding and granulating to obtain a flame retardant masterbatch for use as a flame retardant for polypropylene resin;

[0153] S3, mixing glass fiber, dried polypropylene and the flame retardant masterbatch obtained in step S2, forming a sample bar through a screw extruder, and testing the flame retardant property and mechanical property. Among them, the glass fiber, polypropylene and flame retardant masterbatch account for 20%, 50% and 30% of the sample bar mass respectively.

[0154] At this time, the vertical combustion level of the obtained sample is UL-94 V-1 level, and the mechanical properties are improved by 18%. Compared with Example 1, it can be seen that no ultrafine active iron carbonate is added to the flame retardant, OBDPE is not added to melt and dissolve DBDPE, and the flame retardant DBDPE is not ball-milled. The flame retardant is extremely unevenly dispersed during the extrusion process and has a large particle size. The mechanical properties are reduced by 16% compared with Example 1, and the flame retardant performance of the sample is reduced to UL-94 V-1 level.

[0155] Therefore, the present invention adopts the above-mentioned preparation and application method of the brominated flame retardant masterbatch to dissolve the high melting point flame retardant DBDPE in the low melting point OBDPE, and achieve molecular level / nanoscale dispersion with the resin, thereby eliminating the pollution of HBr gas to the environment, reducing the amount of flame retardant used, improving the heat resistance temperature of the resin, and reducing the production cost.

[0156] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a brominated flame retardant masterbatch, characterized in that: The specific steps include: S1, put octabromodiphenyl ether OBDPE and decabromodiphenyl ethane DBDPE powder into a reactor, heat up until OBDPE melts, OBDPE liquid dissolves DBDPE to form DBDPE-OBDPE solution DOS, add active ultrafine ferrous carbonate powder to DOS under strong stirring, stir and mix evenly to form a dispersion slurry, discharge the slurry while hot, cool to obtain a solid mixture of DBDPE, active ultrafine ferrous carbonate powder and OBDPE that is uniformly dispersed at the molecular level / nanoscale, and crush it into primary powder; S2, putting the primary powder of the mixture obtained in step S1, the synergistic flame retardant and the acid absorbent into an omnidirectional planetary ball mill according to a certain proportion, and milling them to obtain a mixed flame retardant; S3, placing the mixed flame retardant obtained in step S2, the compatibilizer, the lubricant, and the dry resin in a high-speed mixer and mixing them evenly; S4, adding the mixture obtained in step S3 into the hopper of a screw extruder, extruding, and granulating to obtain a brominated flame retardant masterbatch; In the step S1, the mass ratio of DBDPE to OBDPE is 1:1 - 5:1, and the temperature of melting OBDPE and dissolving DBDPE in the reactor to form liquid DOS is 170 - 200 °C; The active ultrafine ferrous carbonate in step S1 is an ultrafine powder surface-modified with hexadecyltrimethylammonium bromide, sodium dodecylsulfonate, a silane coupling agent, and a titanate coupling agent. The particle size of the ultrafine ferrous carbonate powder is in the range of 100 nm to 900 nm. The addition amount of the active ultrafine ferrous carbonate is 0.25 wt% to 5.5 wt% of the total mass of OBDPE and DBDPE.

2. The method for preparing a brominated flame retardant masterbatch according to claim 1, characterized in that: The synergistic flame retardant in step S2 is AO, the acid absorber is HT or talcum powder, and the contents of the primary powder of the mixture, the synergistic flame retardant and the acid absorber in the mixed flame retardant account for 20%-50%, 10%-15% and 0%-20% of the flame retardant masterbatch content, respectively.

3. The method for preparing a brominated flame retardant masterbatch according to claim 1, characterized in that: The compatibilizer in step S3 is a compatibilizer containing a polymer grafted with maleic anhydride or acrylic acid, accounting for 3% of the flame retardant masterbatch content, and the lubricant is stearic acid and silicone masterbatch, which account for 0.5% and 1.5% of the flame retardant masterbatch content, respectively.

4. The method for preparing a brominated flame retardant masterbatch according to claim 1, characterized in that: The resin in step S3 is one of polyethylene, polypropylene, polystyrene, polyamide, polycarbonate, polyethylene terephthalate and polymethyl methacrylate.

5. The method for preparing a brominated flame retardant masterbatch according to claim 1, characterized in that: The maximum extrusion temperature of the screw extruder in step S4 is 10-20° C. higher than the melting point of the resin.

6. An application of a brominated flame retardant masterbatch prepared by the method for preparing a brominated flame retardant masterbatch according to any one of claims 1 to 5, characterized in that: The prepared brominated flame retardant masterbatch is used to flame retard thermoplastic resin.

7. The use of the brominated flame retardant masterbatch prepared by the method for preparing a brominated flame retardant masterbatch according to claim 6, characterized in that: The flame retardant masterbatch is mixed with the resin, and glass fiber is added, wherein the flame retardant masterbatch accounts for 10%-30% of the total addition amount, and the glass fiber accounts for 10%-50% of the total addition amount. The mixture is extruded through a screw extruder to obtain a brominated flame retardant strip.

Citation Information

Patent Citations

  • Preparation process of environment-friendly flame-retardant polystyrene material

    CN115044140A

  • Flame-retardant polyamide elastomer material as well as preparation method and application thereof

    CN115850958A